Testing the Teleological Argument with Bayes’ Theorem: An Evaluation of Wesley Salmon's Argument - Yildiz, İ. (Ankara University, Journal of the Faculty of Divinity, 2022)
The existence of God is the focus of discussions between theism and atheism. At this point, while various arguments were put forward by theists to justify the existence of God; counterarguments were constructed by atheists. The arguments constructed by atheists generally target the existence of God directly. However, instead of discussing the nonexistence of God directly, some argue based on the idea that an argument put forward in favor of God's existence is in fact against it. We find this kind of argument in the work of Wesley Salmon. Salmon builds his argument on discussions regarding the teleological argument in David Hume’s Dialogues Concerning Natural Religion. Claiming that the teleological evidence is inconsistent in many ways at the point of grounding the existence of God, Salmon based his argument on the idea that the order in the universe is evidence for the absence of God rather than for his existence and tried to strengthen the argument with Bayes’ theorem. In this study, the argument that tries to strengthen the claim that the teleological proof indicates the non-existence of God with Bayes’ theorem will be scrutinized and evaluated. In doing so, first, Bayes’ theorem and the teleological proof will be presented briefly to contribute to the clarity of the argument. Afterward, the argument will be explained with its basic premises. Finally, the structure of the argument and the consistency of the ideas on which it is based will be discussed. As a result, it is concluded that the use of Bayes’ theorem in an argument against the existence of God does not make the argument stronger. © 2022 University of Bologna. All rights reserved.
Teleolojik Argüman’ın Bayes Teoremiyle İmtihanı: Wesley Salmon’un Argümanına İlişkin Bir Değerlendirme
Keywords: Bayes' Theorem; Philosophy Of Religion; Probability; Teleological Proof; Wesley Salmon